PENGGUNAAN INSTRUKSIONAL TEKNOLOGI MAKLUMAT DAN KOMUNIKASI (TMK) TERHADAP MATA PELAJARAN TERAS - Abd Samad, Noorazman; Razali, Nizamuddin; Wan Ahmad, Wan Mohd Rashid; Jaafar, Fatimah; Ismail, Affero; Ismail, Erfy; Harun, Hairuddin (Online Journal for TVET Practitioners, 2018)
This research is aimed at studying the levels of use of instructional Information and Communication Technology (ICT) in core subjects in eleven secondary day schools in the districtof Muar. This research are identify from three main objective, as skills level, practice level and attitude level in instructional use in core subjects. Its involves 162 respondents varius teachers teaching core subject as Bahasa Melayu, English, Mathematic, History and Science. Instrument used in this research is questionnaire and data is processed using the Statistical Package for Social Science (SPSS) version 21.0. The results reported in the forms of mean, standard deviation, percentage and one-way ANNOVA test. The result showed the levels of use instructional ICT in core subjects in the aspects of skills level, practice level and attitude level are at the average level, with an overall mean score of 3.31, 2.87 and 3.35 respectively. However, the findings shows no significant difference between the skills level, practice level and attitude level in instructional ICT in core subjects, with ANNOVA test values of 0.224, 0.911 and 0.681 respectively. In conclusioan the skills level, practice level and attitude level in the use of instructional ICT in core subjects are at the average level and that there is no significant difference between the skills level, practice level and attitude level of the teachers in the use of instructional ICT in core subjects in secondary day schools in the district of Muar.